LEADERSHIP AND TEACHER RECRUITMENT STRATEGIES IN PESANTREN: BUILDING A SUSTAINABLE EDUCATION SYSTEM - Faizah, Nur; Siswanto; Mutmainnah (Antis-Publisher, 2024)
Objective: This study aims to analyze the impact of visionary leadership and teacher recruitment quality on the sustainability of pesantren in the face of contemporary challenges. Method: Employing a qualitative approach with a case study method, the research involved in-depth interviews and observations at a pesantren. Results: The findings indicate that visionary leadership plays a crucial role in maintaining the relevance of pesantren, particularly through the integration of technology in education while preserving Islamic traditions. Additionally, selective teacher recruitment, focusing on both academic competence and moral character, significantly contributes to shaping students' character and enhancing the overall quality of education. Effective organizational communication is also essential in supporting the pesantren's vision and mission. Novelty: This research highlights the importance of developing adaptive leadership models and robust teacher recruitment systems to ensure pesantren’s sustainability and competitiveness in a globalized era. It offers practical contributions for pesantren management and advances the literature on Islamic education management by emphasizing the balance between tradition and modernity.